Reproductive Biology of Female Pacific Halibut (Hippoglossus stenolepis) in the Gulf of Alaska - Teresa Fish; Nathan Wolf; Timothy Scott Smeltz; Bradley P. Harris; Josep V. Planas (Frontiers in Marine Science, 2022)
Developing a robust understanding of Pacific halibut reproductive biology is essential to understanding the different components (e.g. maturity) that determine the reproductive output of the species and, therefore, for estimating the relative female spawning biomass. With these, effective and proactive management strategies can be designed and implemented to face the large-scale environmental changes to which high-latitude spawning fish are particularly vulnerable. To date, reproductive studies of Pacific halibut have mainly focused on population or regional scales, leaving the specific details of organism-level reproductive development unexamined. The work described here aimed to address information gaps in Pacific halibut reproductive biology by conducting a detailed histological examination of temporal changes in ovarian development over an annual reproductive cycle with special attention to the use of biological indicators ( e.g. oocyte diameter, gonadosomatic index, hepatosomatic index, Fulton’s condition factor, somatic fat) in characterizing female developmental stages and reproductive phases. Our results provide a foundation for future studies directed at improving current maturity estimations by histological assessment and explore models that test the utility of biological indicators to predict maturity in this important fish species.

A comprehensive description of oocyte developmental stages in Pacific halibut, Hippoglossus stenolepis - Teresa Fish; Nathan Wolf; Bradley P. Harris; Josep V. Planas (Journal of Fish Biology, 2020)
Accurate characterization of oocyte development is essential to understanding foundational aspects of reproductive biology and successful management of Pacific halibut ( Hippoglossus stenolepis ). Here this study provides complete histological descriptions for eight oocyte developmental stages in addition to postovulatory follicles and demonstrates the potential for oocyte size frequency distribution to act as a proxy for ovarian developmental stage and future maturity assessments. Importantly, it provides the first histological evidence that Pacific halibut have a group‐synchronous ovarian developmental pattern with determinate fecundity and support for their batch‐spawning strategy.

Chemical Characterization of Territorial Marking Fluid of Male Bengal Tiger, Panthera tigris - B. V. Burger; M. Z. Viviers; J. P. I. Bekker; M. le Roux; N. Fish; W. B. Fourie; G. Weibchen (Journal of Chemical Ecology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)